Rancangan dan Hasil Uji Sistem Perkerasan Pelat Terpaku pada Tanah Lunak Demak - Kusrin; Pratikso; Rochim, Abdul (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2025)
Rigid pavement with nailed-slab system is a replacement for the use of concrete claws with short posts. This study aims to design a prototype of rigid pavement with a nailed-slab system to be applied to soft soil in Demak. Soft soil samples were taken from Guntur, Demak by digging the soil surface ±50 cm. The prototype design began with the manufacture of a test tub measuring 200 x 200 x 150 cm with walls of thin steel plates on the back and sides. The base of the test body is made of thin steel plate and the front of the body is made of glass. At the bottom of the thin steel plate wall there is a water pipe that is used as an outlet water channel. The soil in the test tub that has been in accordance with the density in the field will be cut, so that the elevation is the same as the top of the test tub before the prototype of the pavement plate is placed on it. The prototype schematic of the test piece consists of reinforced concrete with a slab dimension of 120 cm x 120 cm x 10 cm, and a pole as an anchor with a depth of 100 cm and a diameter of 10 cm. Before casting on reinforced concrete, a strain gauge is installed that is tied to the prototype reinforcement, then cast and left for 28 days to make the concrete 100% perfect strength. After that, a loading test was carried out with a monotonic load in the form of a beam measuring 20 cm x 20 cm gradually with an increase in load twice from the previous load. The load is given from 1 kN, 2 kN, and 4 kN, the results show that the greater the load given, the greater the deflection produced.